77 K operation of AlGaAs/GaAs quantum cascade laser at 9 um - Kosiel, Kamil; Bugajski, Maciej; Szerling, Anna; Kubacka-Traczyk, Justyna; Karbownik, Piotr; Pruszyńska-Karbownik, Emilia; Muszalski, Jan; Łaszcz, Adam; Romanowski, Przemek; Wasiak, Michał; et al. (Photonics Letters of Poland, 2009)
The cryogenic-temperature (77 K), pulsed mode operation of GaAs-based quantum cascade laser (QCL) is reported. This has been achieved by the use of GaAs/Al0.45Ga0.55As heterostructure. The laser design followed an ’anticrossed-diagonal’ scheme of Page et al. [1]. The QCL structures were grown by MBE, with Riber Compact 21T reactor. The double trench lasers were fabricated using standard processing technology, i.e., wet etching and Si3N4 for electrical insulation. Double plasmon confinement with Al-free waveguide has been used to minimize absorption losses. Full Text: PDF References: H. Page, C. Becker, A. Robertson, G. Glastre, V. Ortiz, C. Sirtori," 300 K operation of a GaAs-based quantum-cascade laser at ??9 ?m", Applied Physics Letters, vol.78,. 3529 (2001). [CrossRef] P. Harrison,"Quantum Wells, Wires and Dots: Theoretical and Computational Physics, 2nd ed.", Chichester, U.K.: Willey 2005 [CrossRef] K. Kosiel, J. Kubacka-Traczyk, P. Karbownik, A. Szerling, J. Muszalski, M. Bugajski, P. Romanowski, J.Gaca, M. Wójcik, Microelectronics Journal, (2008), in print S. Hofling, V. D. Jovanovic, D. Indjin, J. P. Reithmaier, A. Forchel, Z. Ikonic, N. Vukmirovic, P. Harrison,"Dependence of saturation effects on electron confinement and injector doping in GaAs/Al0.45Ga0.55As quantum-cascade lasers", Appl. Phys. Lett., vol. 88, 251109 (2006) [CrossRef] Ch. Mann, Q. Yang, F. Fuchs, W. Bronner, K. Kohler, J. Wagner," Influence of Injector Doping Concentration on the Performance of InP-Based Quantum-Cascade Lasers", IEEE J. Quantum Electronics, vol. 42, 994 (2006) [CrossRef] H. C. Liu, F. Capasso,"Intersubband transitions in quantum wells ? physics and device applications II", Semiconductors and Semimetals, vol. 66, Academic Press, New York 2000 S. Hofling, R. Kallweit, J. Seufert, J. Koeth, J. P. Reithmaier, A. Forchel," Reduction of the threshold current density of GaAs/AlGaAs quantum cascade lasers by optimized injector doping and growth conditions", J. Crystal Growth, vol. 278, 775 (2005) [CrossRef]